Whole-body vibration and its impact on heavy earth moving machinery operators in opencast coal mines - Kumar, Vivekanand (IIT(BHU) Varanasi, 2021)
Abstract is available in content.
Keywords: Whole-body vibration; and its impact on heavy earth moving machinery; operators in opencast coal mines